The Application of Remote Sensing and Geographic Information System for Monitoring Changes in Mangrove Forest Area in Torosiaje Village - Agustina; Fitriyanti Bulotio, Nur (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2023)
This study aimed to analyze the changes in the area of mangrove forests over the last 5 years (starting from 2019-2023) and formulate management strategy directions for those damaged in Torosiaje Village, Popayato District, Pohuwato Regency. The method used was image interpretation and interviews. Landsat 8 image interpretation method for changes in mangrove cover area over the last 5 years. Methods of interviewing and filling out questionnaires to related agencies and the local community in Torosiaje Village. Data analysis used SWOT analysis to determine the strategic direction for mangrove management. The result of the image interpretation showed that the area of mangrove forest in Torosiaje Village in 2020 saw a reduction in the area of 1.04 Ha from 2019. In 2021, there was an increase in the area of 1.68 Ha since 2020, and in 2022, there was another increase of 1.68 Ha. 3.13 Ha since 2021, and in 2023, there was another increase of 6.86 Ha since 2022. Meanwhile, the results of the priority analysis of mangrove ecosystem management strategies in Torosiaje Village are based on the results of the analysis carried out; 3 things become tactical decisions for recommendations in management efforts regarding the mangrove ecosystem, such as increasing public knowledge and awareness about the function of the mangrove ecosystem as well as the skill of the community around the mangrove area, strengthening the institutional management of the mangrove ecosystem area and Torosiaje tourism, creating a waste and waste processing system